2014
DOI: 10.7205/milmed-d-14-00064
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Obesity: A Case–Control Study of Young Adult Singaporean Males

Abstract: A case-control study among Singapore Armed Forces' newly enlisted Servicemen was conducted to examine factors associated with male obesity. Four hundred and fifty-nine individuals from the Obese Basic Military Training program were selected as "cases" (average age: 19.5, body mass index: 30.4) and another 340 individuals were selected from the Normal Basic Military Training program as "controls" (average age: 19.3, body mass index: 21.4). Information such as family background, socioeconomic factors, and lifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…Family history of obesity was another predictor of overweight and obesity in this study. study Shi et al (2014), found the same nding, in which the odds of being overweight and obesity were higher in the respondents with history of having obese sibling and obese mother (p < 0.001) as compared to those with no family history [7] . Family history is a complex factor with underlying genetic predisposition, which re ects the effect of shared genetics and environment among close relatives [42] .…”
Section: Demographic Characteristicsmentioning
confidence: 69%
See 1 more Smart Citation
“…Family history of obesity was another predictor of overweight and obesity in this study. study Shi et al (2014), found the same nding, in which the odds of being overweight and obesity were higher in the respondents with history of having obese sibling and obese mother (p < 0.001) as compared to those with no family history [7] . Family history is a complex factor with underlying genetic predisposition, which re ects the effect of shared genetics and environment among close relatives [42] .…”
Section: Demographic Characteristicsmentioning
confidence: 69%
“…In military institutions worldwide, sociodemographic factors [5,6] , family history of obesity [7] , lifestyle factors such as diet intake [8] , physical activity [9] , sleep quality [10] , stress factor [11] and readiness to change factor [12] are often associated with overweight and obesity. However, in the military organization in Malaysia, previous studies only reported the relationship between socio-demographic to overweight and obesity [4] , rendering the relationship with other factors left unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The family background was found to be an obesity risk factor (OR = 1.86 for mother; OR = 2.98 for sib-lings) among Chinese male youths [12]. A significant difference (p < 0.01) was observed between the subjects having the obesity family history and non-obese controls in rs2348071 heterozygous genotype frequencies at the PSMA3 locus [6].…”
mentioning
confidence: 90%
“…In military institutions worldwide, sociodemographic factors [5,6], family history of obesity [7], lifestyle factors such as diet intake [8], physical activity [9], sleep quality [10], stress factor [11] and readiness to change factor [12] are often associated with overweight and obesity. However, in the military organization in Malaysia, previous studies only reported the relationship between socio-demographic to overweight and obesity [4], rendering the relationship with other factors left unknown.…”
Section: Introductionmentioning
confidence: 99%